Cooperative Development and Land Use Planning Dynamics in Sub-Saharan Africa: A Quest for Socio Solidarity Economy and Partnership in Sustainable Urban Development - Magigi, W.; Bee, K. Faustine; Danda, E. B. (IntechOpen, 2012)
None